Maturation and integration of adult born hippocampal neurons: signal convergence onto small Rho GTPases - Vadodaria, Krishna; Jessberger, Sebastian (Frontiers in Synaptic Neuroscience, 2013)
Adult neurogenesis, restricted to specific regions in the mammalian brain, represents one of the most interesting forms of plasticity in the mature nervous system. Adult-born hippocampal neurons play important roles in certain forms of learning and memory, and altered hippocampal neurogenesis has been associated with a number of neuropsychiatric diseases such as major depression and epilepsy. Newborn neurons go through distinct developmental steps from a dividing neurogenic precursor to a synaptically integrated mature neuron. Previous studies have uncovered several molecular signaling pathways involved in distinct steps of this maturational process. In this context, the small Rho GTPases, Cdc42, Rac1 and RhoA have recently been shown to regulate the morphological and synaptic maturation of adult-born dentate granule cells in vivo. Distinct upstream regulators, including several growth factors that modulate maturation and integration of newborn neurons have been shown to also recruit the small Rho GTPases. Here we review recent findings and highlight the possibility that small Rho GTPases may act as central assimilators, downstream of critical input onto adult-born hippocampal neurons contributing to their maturation and integration into the existing dentate gyrus circuitry.